2017
DOI: 10.4314/ahs.v16i4.31
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with community-acquired urinary tract infections among adults attending assessment centre, Mulago Hospital Uganda

Abstract: Background: Urinary tract infections (UTI) are a common medical problem affecting the general population and thus commonly encountered in medical practice, with the global burden of UTIs at about 150 million people. Because uropathogens largely originate from colonic flora, they are easy to predict, and this is the rationale for empirical treatment in Community Acquired-UTI (CA-UTIs). With the increasing prevalence of drug-resistant bacteria among adults with CA-UTI in Uganda, it is no longer adequate to manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
48
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 11 publications
(10 reference statements)
19
48
3
1
Order By: Relevance
“…This substantial sensitivity of nitrofurantoin shown in this study is in conformity with previous reports of Odoki et al (2015) and Ekwealor et al (2016) who reported 78/103 (75.7%) and 191/212 (90.1%) sensitivities respectively. The sensitivity shown by nitrofurantoin in our study is in agreement with study done by Kabugo et al (2016) who reported 12/18 (66.7%) sensitivity of uropathogens to nitrofurantoin. This study demonstrated that the prevalence of MDR strains observed in the Klebsiella spp.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This substantial sensitivity of nitrofurantoin shown in this study is in conformity with previous reports of Odoki et al (2015) and Ekwealor et al (2016) who reported 78/103 (75.7%) and 191/212 (90.1%) sensitivities respectively. The sensitivity shown by nitrofurantoin in our study is in agreement with study done by Kabugo et al (2016) who reported 12/18 (66.7%) sensitivity of uropathogens to nitrofurantoin. This study demonstrated that the prevalence of MDR strains observed in the Klebsiella spp.…”
Section: Discussionsupporting
confidence: 93%
“…The Gram negative bacteria demonstrated 56/56 (100.0%) resistance to erythromycin, this finding is more similar to previous reports by Kyabaggu et al (2007); Kibret and Abera, (2011) and Adwan et al (2014). The Gram positive bacteria resistance to erythromycin of 18/30 (60.0%) reported in this study is more comparable to previous report by Kabugo et al (2016). The resistance of 74/86 (86.0%) to co-trimoxazole in this study is in agreement with previous reports of Odoki et al 2015 Katongole et al (2015) who reported 90/103 (87.4%), 10/14 (71.4%) and 7/8 (87.5%) respectively.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations